Intercropping studies in Indian mustard (Brassica juncea) in the western parts of Uttar Pradesh - Kumar, Adityandra; Chauhan, S.K.; Singh, S.K; Kumari, Nitu (Annals of Agricultural Research, 2014)
A field experiment was conducted during rabi seasons of 2006-07 and 2007-08 at Research Farm of R.B.S. College of Agriculture, Bichpuri, (U.P.) to work out productivity and economics of intercropping of different pulses, linseed and potato with mustard (Brassica juncea) on sandy loam soils of Agra region. Soil of the experimental plots was sandy loam in texture, with pH 7.9, poor in organic carbon (0.30%) and medium in P and K status (15.6 kg P2O5 and 214.2 kg K2O/ha). The treatments were replicated four times in randomized block design with plot size of 5.0m Ã— 3.6 m. The results showed that mustard yield was significantly higher when grown as a sole crop than that grown as intercrop with other crops. Among the intercropping treatments, intercropping of pulses and linseed with mustard produced significantly higher yield of mustard than that of intercropping with potato. Also, in terms of net return it was found that intercropping of potato with mustard in 1:3 row proportion was found better than sole crop of mustard thus showing the higher degree of efficiency and compatibility of the said intercropping treatment.